Medieval queenship - Earenfight, Theresa (History compass, 2017)
This essay surveys new identities and frameworks for the study of medieval queens that have emerged over the past 30 years and argues that the study of queens and the practice of queenship has transformed the study of monarchy. Queenship is understood by most scholars to be a cluster of customs, practices, and political theory that focuses on who queens were and what they did; how they were perceived by their peers; and how they were vital to family, culture, religion, and economics in the European Middle Ages. Empirical research on queens and empresses cuts across time and space and is grounded in feminist theory and methods; it rejects traditional masculine-centered political history in favor of a nuanced understanding of women and power.